Assessing changes in knowledge, attitudes, and intentions to use family planning after watching documentary and drama health education films: a qualitative study - Mubangizi, Vincent; Plastow, Jane; Nakaggwa, Florence; Nahabwe, Haven; Natukunda, Sylvia; Atim, Fiona; Mawere, Brenda; Laughton, Matthew; Muller, Ingrid; Owokuhaisa, Judith; Coates, Sabine; Chambers, Isabella; et al. (https://doi.org/10.1186/s12978-022-01370-5, 2022)
There is a paucity of literature on the effectiveness of drama or documentary films in changing knowledge, beliefs, attitudes, and behavior of people towards family planning. This study aimed to compare and assess the acceptability of health promotion films based on documentary or drama, and their effect on knowledge, attitudes, and intention to use family planning. Methods: We developed short documentary and drama films about contraceptive implants, using the person-based approach. Their acceptability was assessed in focus group discussions with younger women below 23 years, women over 23 years, men of reproductive age, and health workers in four different areas of Uganda (Bwindi/Kanungu, Walukuba/Jinja, Kampala, and Mbarara). Transcripts of the focus group discussions were analyzed using thematic analysis, to generate themes and examine the key issues. We assessed changes in knowledge, attitudes, and intentions to use family planning after watching the films. Results: Sixteen focus groups with 150 participants were carried out. Participants said that the documentary improved their knowledge and addressed their fears about side effects, myths, and implant insertion. The drama improved their attitudes towards the implant and encouraged them to discuss family planning with their partner. The final versions of the documentary and the drama films were equally liked. Conclusions: Viewing a short documentary on the contraceptive implant led to positive changes in knowledge, while a short drama improved attitudes and intentions to discuss the implant with their partner. The drama and documentary have complementary features, and most participants wanted to see both.
Keywords: Post-partum; Family planning; Uganda; Implant; Drama; Documentary; Films; Health promotion